Defying Gravity: What Drives Productivity in Remote Teams? - Thomas Fackler; Michael Hofmann; Nadzeya Laurentsyeva (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
How can teams organize for productive online collaboration? The coronavirus pandemic has led to a large and persistent shift toward remote work. Using fine-grained data from the world's largest platform for open-source software development, we find that the pandemic reduced the productivity of previously co-located teams substantially, whereas similar teams with remote work experience remained resilient. While access to remote talent and experience are important for overall team success, our results highlight the crucial role of communication for productive online collaboration. We find suggestive evidence that, with their peers shifting to online work, remote workers become better integrated into their teams' communication. We conclude that while teams' performance may suffer from the shift to remote work, setting up systems for effective online communication can help mitigate productivity loss.
Keywords: J01; M54; O30; F14; 330; gravity model; open source; knowledge workers; knowledge flows; remote work; online labor markets; COVID-19